Answer:
y= 2x + 8 , y = 4x - 2
2x + 8 = 4x - 2
8 = 2x - 2
10 = 2x
5 = x
Step-by-step explanation:
x = 5
y = 2x + 8
substitute the y in the other expression with this expression (you can do it vise versa too but i chose this because it was first)
goal is to isolate the variable
add 2 to both sides (this cancels out the -2 on the right side)
2x + 8 + 2 = 4x - 2 + 2
2x + 10 = 4x + 0
2x + 10 = 4x
subtract -2x from both sides (cancels out the 2x on the left side)
2x - 2x + 10 = 4x - 2x
0x + 10 = 2x
divide both sides by 2 (cancels out the 2 on the right side)
10 ÷ 2 = 2x ÷ 2
5 = 1x
variable is isolated and tells us that x = 5
B
There are no repeating values for x, for different values plugged in for y.
Answer: frequency